Advanced frequency support strategy of photovoltaic system considering changing working conditions. Issue 2 (27th November 2017) - Lyu, Xue; Xu, Zhao; Zhao, Jian; Wong, Kit Po
Abstract : A novel system frequency support strategy is proposed for the two‐stage three phase photovoltaic generation system, which involves simultaneously utilising a direct current (DC)‐link capacitor and deloading generation output. When frequency variation is detected, the energy stored in an inverter DC‐link capacitor is utilised to enable virtual inertia characteristic for system frequency support. At the same time, a deloading control strategy is also activated to provide system frequency support based on reserved generation beforehand. To address impacts due to the changing working conditions with respect to irradiance and ambient temperature, a variable droop scheme is designed for dynamically adjusting the frequency regulation ability based on deloading. Case studies using a microgrid system embedded with a solar and diesel generator are carried out to verify the effectiveness of the proposed control strategy.